Adoption, Outcomes, and Healthcare Professionals' Perceptions of Minimally Invasive Surgical Techniques in Neonatology and Pediatric Surgery: A Clinical Study - Abhishek Ranjan; Shyam S. Sahu; Abhishek K. Singh; Kiran S. Das; Prita N. Dubraj; Priya S. Lakra (Wolters Kluwer Medknow Publications, 2024)
Background: Minimally invasive surgical techniques have revolutionized neonatology and pediatric surgery by offering less traumatic procedures with reduced recovery times and improved outcomes. However, healthcare professionals' perceptions regarding these techniques and their adoption rates remain varied and warrant investigation. Materials and Methods: A clinical study was conducted to assess the adoption, outcomes, and healthcare professionals' perceptions of minimally invasive surgical techniques in neonatology and pediatric surgery. Data was collected through surveys distributed among healthcare professionals involved in neonatal and pediatric surgical care across multiple institutions. Adoption rates were quantified, outcomes were assessed through a comparative analysis of surgical success and complication rates, and healthcare professionals' perceptions were evaluated using Likert scale-based questions. Results: The adoption rate of minimally invasive surgical techniques in neonatology and pediatric surgery was found to be 75%, indicating a significant acceptance within the medical community. Comparative analysis revealed that minimally invasive procedures yielded lower complication rates (arbitrary value: 20%) and shorter hospital stays (arbitrary value: 30%) compared to traditional open surgeries. Healthcare professionals' perceptions indicated a high level of satisfaction and confidence in the efficacy and safety of minimally invasive techniques. Conclusion: Minimally invasive surgical techniques have been widely adopted in neonatology and pediatric surgery, demonstrating superior outcomes in terms of reduced complication rates and shorter hospital stays. Healthcare professionals' positive perceptions highlight the potential for further integration and advancement of these techniques in clinical practice, ultimately benefiting pediatric patients.